Hypoxia after transarterial chemoembolization may trigger a progenitor cell phenotype in hepatocellular carcinoma. Issue 4 (20th April 2015) - Lai, Jin‐Ping; Conley, Andrew; Knudsen, Beatrice S; Guindi, Maha
Abstract : Aims: To test the hypothesis that the hypoxia marker carbonic anhydrase IX (CAIX), and the cholangiocytic/progenitor markers cytokeratin (CK) 19 and epithelial cell adhesion molecule (EpCAM), may be expressed in areas of hypoxia in hepatocellular carcinoma (HCC) after transarterial chemoembolization (TACE). Methods and results: Immunohistochemistry for CAIX, CK19 and EpCAM (BerEP4) was performed in 57 HCCs, including 40 residual/recurrent tumours adjacent to the TACE treatment site and 17 untreated tumours from the same 40 patients. CAIX was exxpressed in 19 of 40 residual/recurrent HCCs and in two of 17 untreated HCCs. The rate of CAIX immunoreactivity in the treated tumours was significantly higher than that in the non‐treated tumours (47.5% versus 11.8%, P = 0.015). CK19 and EpCAM were expressed in six of 19 and in seven of 19 CAIX‐positive TACE‐treated HCCs, respectively, but were not expressed in CAIX‐negative tumours or untreated tumours. There were significant associations between CK19 and CAIX immunoreactivity, and between EpCAM and CAIX immunoreactivity ( P = 0.007 and P = 0.003, respectively). Double staining of CAIX and CK19 showed co‐localization of both proteins in five of six cases. Three of seven EpCAM‐positive tumours were also positive for CK19. Conclusions: Hypoxia may trigger the expression of proteins that are normally associated with cholangiocytic/progenitor cell differentiation, suggesting that TACE paradoxically causes an aggressive tumour phenotype.